2016
DOI: 10.1186/s12868-016-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel causes degeneration of both central and peripheral axon branches of dorsal root ganglia in mice

Abstract: BackgroundPeripheral neuropathy is a common and dose-limiting side effect of many cancer chemotherapies. The taxane agents, including paclitaxel (Taxol®), are effective chemotherapeutic drugs but cause degeneration of predominantly large myelinated afferent sensory fibers of the peripheral nervous system in humans and animal models. Dorsal root ganglia (DRG) neurons are sensory neurons that have unipolar axons each with two branches: peripheral and central. While taxane agents induce degeneration of peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(53 reference statements)
3
20
0
Order By: Relevance
“…In the current work, the number of CD68-immunopositive macrophage in nerve fibers was significantly increased in the DA group compared with the control group. This is indicative of an increased number of CD68-positive activated macrophages, as has been previously reported as a characteristic of DPN [22] and other human peripheral neuropathies, including axonal neuropathies [23]. It has been reported that the formation of advanced glycation end products may be the cause of many diabetic complications.…”
Section: Discussionsupporting
confidence: 72%
“…In the current work, the number of CD68-immunopositive macrophage in nerve fibers was significantly increased in the DA group compared with the control group. This is indicative of an increased number of CD68-positive activated macrophages, as has been previously reported as a characteristic of DPN [22] and other human peripheral neuropathies, including axonal neuropathies [23]. It has been reported that the formation of advanced glycation end products may be the cause of many diabetic complications.…”
Section: Discussionsupporting
confidence: 72%
“…6). The increased Ca 2þ entry induced by taxanes may in turn activate Ca 2þ -sensitive proteases, leading to the degeneration of peripheral and central branches of dorsal root ganglia axons, as observed previously (3,4). We have already reported that the SK3 channel, which is expressed in dorsal root ganglion neurons (13), promotes Ca 2þ entry and the activity of Ca 2þ -activated proteases calpains (9).…”
Section: Discussionmentioning
confidence: 72%
“…Several hypotheses have been postulated including different taxane metabolisms between patients resulting in an increased drug exposure for some patients or the existence of a direct drug toxicity on peripheral neurons. Paclitaxel was actually found to cause degeneration of peripheral and central branches of dorsal root ganglia axons (3), and this effect may be mediated by the activation of the Ca 2þactivated proteases calpains (4). Because Ca 2þ concentration is regulated by ion channels, another hypothesis is that taxanes neurotoxicity may involve ion channels regulating Ca 2þ homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies suggests that PTX treatment increases presynaptic metabotropic glutamate receptor 5 (mGluR5) activity at spinal cord level that serves as upstream signaling for protein kinase C (PKC)-mediated tonic activation of presynaptic N-methyl-D-aspartate receptors (NMDARs), leading to increased nociceptive input from primary afferent nerves and development of neuropathic pain 30,31 . Unlike, peripheral sensory neurons, spinal cord neurons are unable to regenerate 67,70 and our data suggests that PTX causes neuronal death and this could be addressed in part by developing sustained release formulations (Figure 4a, b).…”
Section: Histopathology and Immunofluorescencementioning
confidence: 92%